Territories of Inequalities and Well-being | TIWELL - Mauritti, R; Botelho, M.C.; Nunes, N.; Neto, P.; Craveiro, D.; Silva, S. F.; Cabrita, L. (2019)
How should we evaluate, measure and direct the progress of societies? Current economic growth is not inclusively and equitably distributed (OECD, 2015; Alvaredo, Chancel, Piketty, Saez, & Zucman, 2018; Boushey, 2019) and traditional economic performance indicators are not sufficient to measure improvements in well-being, equal opportunities, economic security or public confidence (Philipsen, 2015; Sachs, 2015; OECD, 2018; Stiglitz, Fitoussi & Durand, 2018a, 2018b). Taking into account the effects on living conditions and well-being through a perspective that necessarily also incorporates a place-based vision of regions and populations constitutes a crucial scientific and political challenge for the future of societies (Fleurbaey & Bouin, 2018; United Nations, 2019a). It was also within this paradigm that the 2015 Paris Agreement on Climate Change was produced– as a result of COP 21 meeting -, and the United Nations 2030 Agenda for Sustainable Development was prepared. It is on these global challenges that the TIWELL project (which means “Territories of Inequalities and Well-being”) is focused. At the analytical-substantive level, we aim to produce contributions in the delimitation and measurement of a system of indicators that allows a deeper analysis of these issues, simultaneously, in its different dimensions and levels. Such procedures are based on a theoretical-conceptual orientation that dives into the particularities of a historically situated empirical reality, through a relational and multidimensional model, configured by the effect of relational mechanisms of production and reproduction of social inequalities.